Implementasi Kebijakan Kawasan Tanpa Rokok dalam Pencegahan Stunting di Kota Malang - Alliya Safitri; Alfi Haris Wanto; Tjahjanulin Domai (Research and Development Agency Ministry of Home Affairs, 2025)
Indonesia has a high prevalence of smoking, which adversely affects public health, particularly children and pregnant women. Exposure to secondhand smoke is a significant risk factor for stunting among toddlers. This study evaluates the implementation of the Smoke-Free Area (SFA) policy in Malang City as a strategy to reduce smoke exposure and prevent stunting. A qualitative descriptive approach using Grindle’s policy implementation theory was employed to assess the roles of government, society, and the private sector. The findings indicate that while the SFA policy has been adopted across public and private sectors, enforcement effectiveness and household compliance remain low. Cultural factors, limited resources, and weak coordination pose significant challenges. Nevertheless, the stunting prevalence decreased from 25.7% in 2021 to 17.3% in 2023, suggesting that the policy has had a positive impact. Strengthening resources, education, and law enforcement is essential to enhance the policy’s effectiveness in preventing stunting.